Pesantren, Dinamika, dan Tantangan Global: Analisis UU Pesantren No.18 Tahun 2019 - Diana Handayani (UIN Mataram, 2022)
The purpose of this article is to discuss 1) the background to the passing of the Undang-Undang Pesantren (UU Pesantren [Islamic Boarding School Law]) no. 18 of 2019; 2) the implementation analysis of the UU Pesantren, and 3) the positive impact of the stipulation of the UU Pesantran. The type of method or approach used in writing this article is library research. The findings of this article state that the positive impacts of passing the Islamic Boarding School Law are: 1) providing recognition, affirmation, and facilitation; 2) graduates are equivalent to other formal education; 3) maintaining independence, and 4) having a large enough space and role in the field religious. As for the negative impacts, namely: 1) pesantren that do not have an establishment permit are not recognized and can be disbanded; 2) offend the authority of the Kyai; 3) this 'new' regulation does not seem to take into account the diversity of pesantren in Indonesia, and 4) is not transparent or open regarding funding. Keywords: Islamic Boarding School Law, Dynamics, and Global Challenges Tujuan artikel ini ialah untuk membahas 1) latar belakang disahkannya Undang-undang Pesantren No 18 Tahun 2019; 2) analisis implementasi dari UU Pesantren, dan 3) dampak ditetapkannya UU Pesantren tersebut. Jenis metode atau pendekatan yang digunakan dalam tulisan artikel ini adalah studi kepustakaan. Hasil temuan artikel ini menyebutkan bahwa dampak positif disahkannya UU Pesantren, yaitu: 1) pemberian pengakuan (rekognisi), afirmasi dan fasilitasi 2) lulusan setara dengan pendidikan formal lainnya, 3) menjaga independensi, 4) memiliki ruang dan peran yang cukup besar dala bidang keagamaan. Adapun dampak negatifnya, yaitu: 1) pesantren yang tidak memiliki izin pendirian tidak diakui dan dapat dibubarkan, 2) menyinggung otoritas Sang Kyai, 3) peraturan 'baru' ini nampak seperti tidak memperhitungkan keberagaman pesantren di Indonesia 4) tidak transparan atau terbuka mengenai pendanaan.